Status of serum calcium and vitamin D: a comparative study between premenopausal and postmenopausal women - Dhungana, Arun; Man Tamang, Jagat; Pandeya, Arun; Dahal, Sunit; Bhandari, Dinesh (Journal of Chitwan Medical College, 2025)
Introduction: Nowadays, most of the postmenopausal women are experiencing deficiencies in calcium and vitamin D, which has led to an increased risk of osteoporotic fractures.  Prompt estimation of serum calcium, phosphorus, vitamin D, and alkaline phosphatase (ALP) can aid in preventing complications and providing proper treatment. This study aims to compare serum calcium, phosphorus, vitamin D, and ALP levels in premenopausal and postmenopausal women.Method: This was a quantitative cross-sectional study conducted in orthopaedic department at Kathmandu Medical College between 01 July – 31 December 2024. Ethical clearance was taken from Institutional Review Committee. Using consecutive sampling, participants' serum samples were analysed for calcium, phosphorus, and ALP activity using an automated analyser, and vitamin D was analysed using chemiluminescence immunoassays (CLIA) methods. T-test, Anova, Pearson’s correlation and Multiple Linear Regression analysis were calculated using SPSS.Result: Out of 244 participants, Body mass index (24.08±1.51 kg/m2), (p